2021
DOI: 10.3390/fermentation7040263
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Volatile Fatty Acid Production from Oil Palm Empty Fruit Bunch through Acidogenic Fermentation—A Novel Resource Recovery Strategy for Oil Palm Empty Fruit Bunch

Abstract: The glucan-rich fraction, hemicellulosic compounds-rich fraction, and a mixture of both fractions obtained from organosolv pretreatment of oil palm empty fruit bunch (OPEFB) were used as substrates to produce volatile fatty acids (VFAs) in acidogenic fermentation. In this study, the effects of medium adjustment (carbon to nitrogen ratio and trace elements supplementation) and methanogenesis inhibition (through the addition of 2-bromoethanesulfonate or by heat shock) to enhance VFAs yield were investigated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…This could be because the onset of the exponential phase of methanogenesis is typically with a lag phase of about 10 days for food waste . Similarly, Mondylaksita et al (2021) reported acceleration of VFA production after day 10 of fermentation of the glucan-rich fraction of palm oil empty fruit bunch …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be because the onset of the exponential phase of methanogenesis is typically with a lag phase of about 10 days for food waste . Similarly, Mondylaksita et al (2021) reported acceleration of VFA production after day 10 of fermentation of the glucan-rich fraction of palm oil empty fruit bunch …”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the prior inhibition of methanogenesis in an acidic environment, and therefore, heat treatment might have a negligible effect to eliminate methanogenic archaea. Moreover, the acidogenic bacteria can form spores when subjected to high temperatures, whereas methanogens lack that functionality, and therefore, a heat shock at around 80–100 °C for 15–120 min can be employed to deactivate the methanogens . Sarkar et al (2016) reported that heat shock resulted in VFA accumulation because it simultaneously selects acidogens and removes methanogens .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CKM, CM, and FPPL used in the anaerobic batch experiments were thermally treated at 80 °C for 15 min (thermal shock) using a water bath to inhibit the activity and growth of methanogens [25]. The batch assays were carried out under mesophilic conditions (37 ± 1 °C) for 23 days, using 120 mL glass serum bottles as bioreactors.…”
Section: Batch Digestionmentioning
confidence: 99%
“…The CO 2 yields for FPPL at initial pH of 7.90, FPPL at pH 7.56 together with CKM as inoculum and FPPL at pH 7.41, FPPL at pH 7.02 together with CM were similar under the tested conditions and ranged from 7.5 to 14 mL/g VS. Hydrogen gas that is produced and VFAs have some parallels as they are both mediators and precursors to biogas synthesis. As a result, hydrogen gas is typically created as a byproduct of bioprocesses that are advantageous for high-yielding VFA generation, and vice versa [25]. CKM only at pH 7.9 showed the highest H 2 yield of 11.7 mL/g VS. Stabilization of H 2 production occurred shortly after for FPPL with CKM and CM batch reactors (Fig.…”
Section: Batch Digestion Of Fppl To Vfasmentioning
confidence: 99%